1994
DOI: 10.1111/j.1600-0560.1994.tb00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma: A deficient squamous cell carcinoma? Study of bcl‐2 expression

Abstract: Ten keratoacanthomas with both proliferative and regressive histologic features along with 10 well‐differentiated squamous cell carcinomas were examined using immunohistochemistry for the expression of bcl‐2, a protooncogene recently recognized to be involved in protecting cells from undergoing apoptosis. The squamous cell carcinomas had a modest but diffuse staining pattern, while the proliferative keratoacanthomas stained only at the basal cells and only rare cells stained positively in the regressive kerato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…7,47,48 There are several reports of differential expression of molecular markers, such as laminin-32, nuclear factor kappa B/p50, cortactin, glut-1, Bcl-x, beta-catenin, CD44, anti-P2 X7, K10, E-cadherin, transforming growth factor-a, peanut agglutinin, peanut lectin receptor, and carcinoembryonic antigen, in KAs and SCCs. 22,31,40,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] KAs were consistently positive for K6, K10, and K14. K10 and K14 were observed in specialized cells within the ORS of the hair follicle and in the interfollicular epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…7,47,48 There are several reports of differential expression of molecular markers, such as laminin-32, nuclear factor kappa B/p50, cortactin, glut-1, Bcl-x, beta-catenin, CD44, anti-P2 X7, K10, E-cadherin, transforming growth factor-a, peanut agglutinin, peanut lectin receptor, and carcinoembryonic antigen, in KAs and SCCs. 22,31,40,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] KAs were consistently positive for K6, K10, and K14. K10 and K14 were observed in specialized cells within the ORS of the hair follicle and in the interfollicular epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…24 BCL-2 is a proto-oncogene involved in protecting cells from undergoing apoptosis and has been shown to have decreased expression in regressing keratoacanthomas. 23,25 We hypothesize that prominent enrichment of the clathrin-mediated endocytosis signaling pathway may be because of granzyme-mediated apoptosis. Cytotoxic T cells and natural killer cells utilize lytic effector proteins of perforin and granzymes to eliminate target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors regard KA as a variant of SCC that only rarely progresses into an invasive SCC [2]. The single feature that separates KA from SCC is the involution displayed by KA [3]. KA could represent a "deficient" SCC missing a signal that would allow continued growth or protection against apoptosis and regression [3].…”
Section: An Immunohistochemical Study Of Bcl-2 Protein Expression In mentioning
confidence: 99%
“…This protein can be detected by im- conflicting findings [3][4][5][6][7], Certain investigators have found some degree of positive staining for bcl-2 in ail of their KAs [3j or in only some of them [5]. whereas positive staining for bcl-2 was detected in all of the SCCs [3]. in only some of them [5], or in none at all [4.6,7].…”
Section: An Immunohistochemical Study Of Bcl-2 Protein Expression In mentioning
confidence: 99%
See 1 more Smart Citation